Evaluation of Sodium Hypochlorite Irrigant, Bingpeng Irrigant, and Fufang Bingpeng Irrigant as Endodontic Irrigants During Passive Ultrasonic Irrigation - Shi, Yan; Deng, Zhipeng; Yang, Yulu; Cui, Lanyue; Chen, Tingtao; Hu, Mingjing; Xie, Lei; Yang, Jian (Frontiers in Cellular and Infection Microbiology, 2019)
Given the increasing prevalence of antibiotic resistance among bacterial strains and the side effects caused by synthetic drugs, it is increasingly important to investigate potential herbal alternatives. In the present study, antimicrobial, cell cytotoxicity, and cleaning tests were performed to evaluate the potential of Fufang Bingpeng irrigant as a root canal irrigant, in addition to q-PCR and high-throughput sequencing analyses. Our in vitro results showed a low minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of Fufang Bingpeng irrigant against Porphyromonas gingivalis ATCC 33277 (6.25 and 12.5%, respectively), Prevotella intermedius ATCC 25611 (6.25 and 6.25%, respectively), Fusobacterium nucleatum ATCC 25286 (6.25 and 6.25%, respectively), Enterococcus faecalis ATCC 19433 (25 and 25%, respectively), and Bacteriodes fragilis ATCC 25285 (12.5 and 12.5%, respectively). Furthermore, it effectively removed the remaining debris and increased the number of open dentinal tubules in root canals compared to the NaCl irrigant (p < 0.05). Fufang Bingpeng irrigant also presented low cytotoxicity to L929 cells compared to the NaClO irrigant. The in vivo results indicated that all irrigants used significantly reduced the number of bacteria compared to the number prior to treatment, and only 1/104.95 bacteria remained in the root canal following the use of Fufang Bingpeng irrigant (p < 0.001). Moreover, the high-throughput sequencing results indicated that all irrigants markedly enhanced the α diversity in the root canal compared to the before preparation control group, while Fufang Bingpeng maintained better microbial diversity than other groups. Therefore, Fufang Bingpeng irrigant presents a promising alternative for use as a root canal irrigant in clinical settings.